THE WICKEDNESS OF CASTE PREJUDICE AND ITS CONSEQUENCE IN THE NOVELS OF MULKRAJ ANAND, ARUNTHATHI ROYAND PERUMAL MURUGAN - Sivaprakasam, M.; Jayakumar, J. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction to Indian literature and the writing novels have been untraded enough to exhaustively reflect the history, society, economic and political domain and the tradition of Indian subcontinent navigating since the ages. The novel is one of the genres of literature that everyone recognizes at sight. In spite of uncountable varieties of method and manner, the differences in the appeal it makes to its readers stand clearly apart from any other literary shape. Its medium is prose, not verse; as to content, it is a portrayal of life, in the shape of a story, wholly or in the main as to its way of fictitious; as to its way of portraying life, though the pretence of exact reporting of indiscriminate detail is generally regarded as a mistaken kind of realism, and much latitude is allowed to plot and surprise, everything recounted is required to be credible, or at least to have a definite and unchanging relation to the facts of existence. The Novel is concerned with the real world; its aim is to present a world as like as possible to the actual world, not to fashion a new one to the heart’s desire. Undoubtedly Indian novelists are the creative masterminds behind such ravishing story, plots and nonstop mashes in language. Today Indian Novels have reached to the height of success and secured a notable status not only in Indian market, but also globally. The much has been done in this field yet more is about to do.